2019
DOI: 10.1177/0021955x19864389
|View full text |Cite
|
Sign up to set email alerts
|

Tuning cell structure and expansion ratio of thick-walled biodegradable poly(lactic acid) foams prepared using supercritical CO2

Abstract: Thick-walled poly(lactic acid) samples are foamed using supercritical carbon dioxide as physical foaming agent over a wide saturation time range using a constant-temperature mode and a wide foaming pressure range using the constant-temperature mode and a varying-temperature mode. Using the constant-temperature mode, three regions with no-celled core and two regions with cells of different diameters appear on the fractured surfaces of the foamed samples prepared at 5 and 10 min saturation times, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Cell density and cell size are two important parameters used to evaluate the structural properties of polymeric cellular foams. 12,13 These two parameters have an inverse correlation. The cell density is the number of cells in 1 cm 3 volume of the unfoamed polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Cell density and cell size are two important parameters used to evaluate the structural properties of polymeric cellular foams. 12,13 These two parameters have an inverse correlation. The cell density is the number of cells in 1 cm 3 volume of the unfoamed polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fabricating polymeric foams with bimodal cell structure is a hot topic. So far, the most common methods include controlling foaming conditions (temperature and pressure), various foaming agent combinations, and selecting suitable polymer resins. The main routes for controlling foaming conditions include a two-step depressurization process and a temperature-depressurizing synergistic method in a batch foaming process. For example, polystyrene (PS) foam with bimodal structure can be facilitated by changing the pressure release rates in two stages .…”
Section: Introductionmentioning
confidence: 99%
“…One key strategy is to construct cellular morphology in the polymer matrix. Over the past 10 years, supercritical carbon dioxide (scCO 2 ) has received considerable attention as a foaming agent for polymeric foams owing to its nontoxicity and nonflammability. It is well known that the foaming behavior of semicrystalline polymers is much more complicated than that of amorphous polymers on account of the existence of crystals . The existing crystal regions not only decrease the CO 2 solubility in the matrix but also influence cell nucleation and cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleation step, the interface between crystal phases and amorphous phase is beneficial for CO 2 accumulation, which leads to less Gibbs free energy needed for nucleating at the interface than that necessary for homogeneous nucleation. Meanwhile, in the cell growth step, the formed cells are constrained by the crystal region owing to its stiffness. Among the semicrystalline polymers, PLA foaming behavior under compressed CO 2 has been extensively discussed. ,, Yang et al investigated the effect of crystallinity and crystalline morphology on the cell structure and found that both played an important role in the cell structure. The ring banded spherulite induced by compressed CO 2 in the temperature range of 90–110 °C facilitated to prepare uniform PLA foam.…”
Section: Introductionmentioning
confidence: 99%